2018
DOI: 10.3892/mmr.2018.8601
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA BC168687 small interfering RNA reduces high glucose and high free fatty acid‑induced expression of P2X7 receptors in satellite glial cells

Abstract: Purinergic signaling contributes to inflammatory and immune responses. The activation of the P2X purinoceptor 7 (P2X7) in satellite glial cells (SGCs) may be an essential component in the promotion of inflammation and neuropathic pain. Long non-coding RNAs (lncRNAs) are involved in multiple physiological and pathological processes. The aim of the present study was to investigate the effects of a small interfering RNA for the lncRNA BC168687 on SGC P2X7 expression in a high glucose and high free fatty acids (HG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…ATP can activate phospholipase C, which produces diacylglycerol and induces sensitization of TRPV1 leading to diabetic neuropathy (Chiba et al, 2017). BC168687 siRNA also extensively decreased the expression level (messenger RNA [mRNA] and protein) of TRPV1 receptors in DRG as well as the P2X7 receptor (Liu, Deng, Du, & Xu, 2018), which were confirmed by time quantitative polymerase chain reaction (PCR) and Western blot. Inflammatory cytokines are released more from SGCs of DRG after the activated TRPV1 receptor enables input of Ca+.…”
Section: Lncrnas In Dnp Research Related To P38 Signaling Pathwaysmentioning
confidence: 83%
“…ATP can activate phospholipase C, which produces diacylglycerol and induces sensitization of TRPV1 leading to diabetic neuropathy (Chiba et al, 2017). BC168687 siRNA also extensively decreased the expression level (messenger RNA [mRNA] and protein) of TRPV1 receptors in DRG as well as the P2X7 receptor (Liu, Deng, Du, & Xu, 2018), which were confirmed by time quantitative polymerase chain reaction (PCR) and Western blot. Inflammatory cytokines are released more from SGCs of DRG after the activated TRPV1 receptor enables input of Ca+.…”
Section: Lncrnas In Dnp Research Related To P38 Signaling Pathwaysmentioning
confidence: 83%
“…Additionally, a recent study showed that uc.48+ participate in pain transmission in trigeminal neuralgia, the most common NP in the facial area, via upregulating expression of P2X7 receptor and furthermore enhance the phosphorylation of ERK1/2 [52]. Similarly, BC168687 siRNA inhibited the expression of P2X7 receptors and influenced the pathological process of DNP [53,54]. In another study, MRAK009713 directly interacted with the P2X3 protein expressed in the CCI rat model and potentiated P2X3 receptor function [55].…”
Section: Lncrnas Mediate P2x Receptorsmentioning
confidence: 93%
“…This receptor is engaged both in inflammation and in NP. Researchers have shown that small inhibitory RNA to NONRATT021972, uc.48+, and BC168687 can inhibit the expression of P2X7 receptor expression in a DNP rat model and modulate ion channel expression, thereby alleviating the symptoms of NP [46,47,50,53,54]. In addition, researchers used bioinformatics and found that calcium ion transport was the second most significant biological process of differentiate expressed lncRNAs [24].…”
Section: Lncrnas Alter Np-related Ion Channelsmentioning
confidence: 99%
“…is time-dependent and varies between strains and species [182,183,185]. LncRNAs play important roles in neuropathic pain processes not only in neurons, but also in non-neuronal cells, such as Schwann cells, satellite glial cells, macrophages and microglia [74,83,185,[188][189][190][191].…”
Section: Lncrnas As Possible Signatures For Pain Disordersmentioning
confidence: 99%